Midpalatal suture osteotomy combined with microimplant-assisted rapid palatal expansion for adult maxillary transverse deficiency treatment: a study protocol of a randomised controlled trial - Lei Zhang; Yifeng Qian; Wenyi Zhang; Miri Chung; Yanfei Zhu; Lingyong Jiang (BMJ Open)
Introduction Maxillary transverse deficiency (MTD) is a common type of malocclusion. For adult MTD patients with highly ossified midpalatal sutures, surgically assisted rapid palatal expansion (SARPE) has been the conventional method of maxillary expansion. However, SARPE has the disadvantages of significant trauma, high cost and a high incidence of adverse events. Therefore, we proposed a novel minimally invasive method for maxillary expansion, which is midpalatal suture osteotomy combined with microimplant-assisted rapid palatal expansion (MSO-MARPE). The results are expected to confirm MSO-MARPE as a novel minimally invasive alternative to SARPE in skeletally mature MTD patients.Methods and analysis A prospective, single-centre, parallel-group randomised controlled trial will be conducted, enrolling 20 adult MTD patients. Participants will be randomised equally to the control and experimental groups. The control group will undergo a Lefort I and median osteotomy and postoperative maxillary expansion with a tooth-borne Hyrax-type expander. The experimental group will undergo a midpalatal suture osteotomy and postoperative maxillary expansion with a microimplant-assisted expander. A series of linear and angular parameters will be measured in the pre- and post-coronal planes before treatment (T0), immediately after expansion (T1) and 6 months after expansion (T2) to evaluate the efficacy of skeletal expansion and dental side effects. The study aims to compare the clinical and cost-effectiveness of SARPE and that of MSO-MARPE. The primary outcome is the contribution of posterior midpalatal expansion immediately after expansion. The secondary outcomes include nasal, sutural, alveolar and dental expansion, pain intensity, operative time and treatment costs. The safety indicator will be the number and incidence of adverse events. The interaction between the control group and the experimental group will be analysed using two independent-sample t-tests or Mann–Whitney U test, and the paired data at different time points will be analysed using paired t-test.Ethics and dissemination The trial protocol (version 6.0 13 December 2024) has been approved by the Institutional Review Board of the Ninth People’s Hospital of Shanghai Jiao Tong University School of Medicine (approval number: SH9H-2023-T309-3). Results will be disseminated through peer-reviewed publications and presentations at scientific conferences.Trial registration number ChiCTR2400081545.